2011
DOI: 10.1002/ajmg.a.34015
|View full text |Cite
|
Sign up to set email alerts
|

TGFBR2 deletion in a 20‐month‐old female with developmental delay and microcephaly

Abstract: To date, over 70 mutations in the TGFBR2 gene have been reported in patients with Loeys–Dietz syndrome (LDS), Marfan syndrome type 2 (MFS2), or other hereditary thoracic aortic aneurysms and dissections. Whereas almost all of mutations analyzed thus far are predicted to disrupt the constitutively active C-terminal serine/threonine kinase domain of TGFBR2, mounting evidence suggests that the molecular mechanism underlying these diseases is more complex than simple haploinsufficiency. Using exon-targeted oligonu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The authors concluded that TGFBR2 haploinsufficiency may cause a phenotype that is different from LDS. Duplication of TGFBR1 on the other hand was found in a patient with symptoms suggestive of LDS [Campbell et al, 2011]. These findings are in line with the hypothesis that an increase in TGF ␤ signalling, rather than haploinsufficiency, is the main pathogenetic mechanism underlying LDS, and in part also MFS.…”
Section: Loeys-dietz Syndromesupporting
confidence: 77%
See 1 more Smart Citation
“…The authors concluded that TGFBR2 haploinsufficiency may cause a phenotype that is different from LDS. Duplication of TGFBR1 on the other hand was found in a patient with symptoms suggestive of LDS [Campbell et al, 2011]. These findings are in line with the hypothesis that an increase in TGF ␤ signalling, rather than haploinsufficiency, is the main pathogenetic mechanism underlying LDS, and in part also MFS.…”
Section: Loeys-dietz Syndromesupporting
confidence: 77%
“…So far, no phenotypic differences have been reported between patients with mutations in TGFBR1 or TGFBR2. Recently, a 20-month-old female with microcephaly and developmental delay, but no typical features of LDS, was found to carry a microdeletion including TGFBR2 [Campbell et al, 2011]. The authors concluded that TGFBR2 haploinsufficiency may cause a phenotype that is different from LDS.…”
Section: Loeys-dietz Syndromementioning
confidence: 99%
“…Patients with FSD experience multiple spontaneous self-healing epitheliomas, but do not show craniofacial dysmorphism or vascular disease (Goudie et al 2011). Additionally, a deletion of TGFBR2 has been described in a 20 mo old with microcephaly and developmental delay, but without features of LDS (Campbell et al 2011). In this light, receptor mutations in LDS seemingly select for receptors that must manifest a function separable from simple kinase-mediated signal transduction.…”
Section: Tgf-b Pathway Mutations: Loeys -Dietz Syndrome (Lds)mentioning
confidence: 99%
“…For TGFBR1/2 mutations in LDS, it is becoming increasingly evident that, although the mutations in the serine/ threonine kinase domains of these proteins lead to a loss of function of the kinase activity, a complete haploinsufficiency of TGFBR1 or TGBFR2 does not seem to cause an aortic aneurysm phenotype. 160,161 Furthermore, the currently described nonsense mutations in LDS are all predicted to escape nonsense-mediated decay, and true nonsense mutations in TGFBR1 cause a skin cancer phenotype, multiple self-healing squamous epithelioma. 162 As such, having some mutant protein expressed seems to be a prerequisite to cause an aortic aneurysm phenotype.…”
Section: A Better Understanding Of Pathogenesis Has Engendered Contromentioning
confidence: 99%